(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper briefly describes the performance of Sidronio Sánchez Pineda‘s substitute governor. This work also describes and explains how the political panorama in Michoacán was during the decisive confrontation —initially clandestine but later open— between Pineda’s and Francisco J. Múgica’s group. The article also refers to the immediate antecedents of political and electoral character which allowed and determined the outbreak of the delahuertista rebellion in Michoacán.